Effect of Combined Education on Promoting Nutritional Behaviors of Female Students - Sadegh Khakpour; Sedighehsadat Tavafian; Shamsodin Niknami; Shamsodin Niknami (Hamadan University of Medical Sciences, 2016)
Background and Objectives: Malnutrition is one of the most common health problems around the world, which effects millions of people. This study aimed at determining the effect of an educational program on nutritional behavior of female students (8- to 10-yearolds) in Chabahar, Iran. Materials and Methods: This was a semi-experimental study with before and after method. The statistical population included all 8- to 10-year-old female students of Chabahar, during year 2014. In order to perform the study, 65 female students were selected through simple sampling method and enrolled in the study. Data were collected by a questionnaire consisting of 4 parts, including demographic information and questions concerning nutrition knowledge, attitude and behavior, which was completed before the intervention, immediately, and 2 months after the last intervention. The intervention program was conducted through lectures and using multimedia equipment in three 30-minute sessions. Repeated measures and chi-square tests were applied via the SPSS-16 software to analyze the data. Results: Results showed that the mean score of students' knowledge before, immediately, and 2 months after the intervention was statistically different (P>0.05). However, attitude and behavior of the students were not significantly different (P<0.05). Conclusions: The results showed that the educational program could increase knowledge of the students after 2 months. Further research is required to show the effects of the program on attitudes and behaviors.